2015
DOI: 10.1063/1.4916124
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Reaction History ablator areal density constraints upon correlated diagnostic modeling of National Ignition Facility implosion experiments

Abstract: The inelastic neutron scattering induced γ-ray signal from 12C in an Inertial Confinement Fusion capsule is demonstrated to be an effective and general diagnostic for shell ablator areal density. Experimental acquisition of the time-integrated signal at 4.4 MeV using threshold detection from four gas Čerenkov cells provides a direct measurement of the 12C areal density near stagnation. Application of a three-dimensional isobaric static model of data acquired in a recent high neutron yield National Ignition Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…We have a measure of the total areal density qr of the CH ablator using the Gamma Reaction History (GRH) diagnostic by measuring the c-ray signal from inelastic neutron scattering of 12 C in the ablator material. 20 The N140819 shot showed the lowest carbon qr of any high foot shot. In addition, the capsule x-ray spectrum measured by the Ross pair filters 21,22 can be fit to infer an optical depth (jqr).…”
Section: Fig 4 Neutron Yield Increases With Increased X-ray Drive Omentioning
confidence: 91%
“…We have a measure of the total areal density qr of the CH ablator using the Gamma Reaction History (GRH) diagnostic by measuring the c-ray signal from inelastic neutron scattering of 12 C in the ablator material. 20 The N140819 shot showed the lowest carbon qr of any high foot shot. In addition, the capsule x-ray spectrum measured by the Ross pair filters 21,22 can be fit to infer an optical depth (jqr).…”
Section: Fig 4 Neutron Yield Increases With Increased X-ray Drive Omentioning
confidence: 91%
“…The gamma ray signal can give the time dependence of the product of burn rate times the carbon areal density. Cerjan et al 2 concluded from GRH data that there were smaller remaining ablator mass and higher shell density than calculated. Radio-chemistry offers another method for measuring ablator areal density by using primary materials or adding dopants to the ablator and collecting products from neutron or charged particle induced nuclear reactions.…”
Section: Introductionmentioning
confidence: 89%
“…Techniques for determining the ρR of the unablated plastic or high density carbon (HDC) shell mass at bangtime using previous gas Cherenkov diagnostics have been reported by Hoffman [5,6] and Cerjan [7]. A graphite puck of known density mounted on the front of GCD-3 allows for an in situ calibration of the detector response to 4.44 MeV 12 C(n,n') inelastic scatter gamma rays.…”
Section: Neutron Induced Gamma Ray Studies Using "Pucks" Mounted On Gmentioning
confidence: 99%